Sosialisasi Bahaya Merokok Di SMA Negeri Lawe Sumur Kabupaten Aceh Tenggara - Afrizal Afrizal; Muhammad Tahir; Saddam Hasrul; Ladipin Ladipin; Habibul Akram; Orbit Irwansyah (COVIT (Community Service of Tambusai), 2023)
Community service with the topic Socialization of the Dangers of Smoking at Lawe Sumur State High School has been carried out and succeeded well. The participation of students in participating in this court activity was very enthusiastic because the attendance rate of participants reached 100% (130 students) according to the target. The results of this outreach activity showed an increase in participants' knowledge after participating in this activity by 14.62%. Keywords: socialization, danger, smoking, Kutacane